A study of the doping process in Li4Ti5O12 and TiO2 battery electrode materials studied in the ion-gated transistor configuration - Garza, José Ramón Herrera; Camargo, Luan Pereira; Azari, Ramin Karimi; Neres, Lariel Chagas da Silva [UNESP]; Khaleel, Shahid; Barbosa, Martin Schwellberger; Soavi, Francesca; Santato, Clara (Royal Society of Chemistry (RSC), 2023)
Understanding how the electronic conductivity of metal oxides used as electrode materials in Li-ion batteries (LIBs) evolves as a function of the degree of lithiation/delithiation is relevant to try to prolong the battery lifetime, which affects, among others, the sustainability of LIBs. We propose the use of ion-gated transistors (IGTs) employed as transistor channel material films of Li4Ti5O12 (LTO) and TiO2 interfaced to the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]) including the salt LiTFSI, to study the evolution of the doping mechanism, charge carrier density and mobility with the advancement of lithiation/delithiation in the films. The process of lithiation/delithiation is controlled by the electrical bias applied at the gate electrode, made of carbon paper coated with high surface area activated carbon. The sweeping rate of the gate bias affects the kinetics of Li intercalation/deintercalation and, consequently, the electronic doping of the transistor channel. We discuss how different doping mechanisms, namely electrostatic, “purely” electrochemical, or electrochemical possibly associated with structural changes in the transistor channel are possible for the metal oxide films. We consider such a discussion relevant to contribute to the optimal use of the electrode materials in LIBs.